[Logging in Palawan ; Game of the generals ; Nonoy Marcelo [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1988)
Tackles logging activities of alledged businessman in Palawan; controversy between Gen. Alfredo Lim and Gen. Almonte regarding the intervention of the WPD in a smuggling bust by EIIB; and the philosophy and creative talent of the creator of "Tisoy", Bubwit and cartoon characters that comment on political events in the Philippines.
Logging in Palawan (17 min.) -- Game of the generals (16 min.) -- Nonoy Marcelo (12 min.)
VHS.
Keywords: Marcelo, Nonoy; Logging -- Philippines -- Palawan; Cartooning; Smuggling -- Philippines